Short stories of Mulk Raj Anand: A Storehouse of Indian Myths and Traditions - RUPAL a. FARISTA (Dr. Chinmay Pandya, 2014)
Our traditions and beliefs give rise to many myths. Many a times the Indian authors used their knowledge about myths and traditions and made stories based on them. Mulk Raj Anand is also highly traditional author who was impressed by the stories told to him as a child by his grandmother and he uses the mythical tales in his short stories. By reading these short stories, any reader is also acquainted with the traditional myths of our country. This article is an endeavor to bring to notice various myths used by Anand in his various short stories and the effect of these myths on the readers. Anand also tries to show the effect of the traditional beliefs and customs on the Indian women and proclaims the fact that women had to suffer at many places on the name of customs and traditions. In the veil of the beliefs and traditions of the family or castes, women were subjected to many forms of injustices and they too accepted all the torture on the name of custom. Dowry, Sati and harassment to widows are some of the common features he uses in his stories to depict the predicament of Indian women in the 20th century. He has also drawn attention of the readers towards the abusive language used for the women at that time. These stories help us analyze the status of women of India in the 20th century.